Ethical Curriculum Development: Insights From Islamic Epistemology Towards Sustainable Development Goals (SDGs) - Muhammad Abuzar; Mahmudulhassan; Saif Uddin Ahmed Khondoker (Universitas Muhammadiyah Surakarta, 2024)
Objective: This study aims to explore the integration of Islamic epistemology in ethical curriculum development to support the achievement of Sustainable Development Goals (SDGs). The research focuses on aligning ethical values derived from Islamic teachings with modern educational practices, offering a transformative framework that contributes to global sustainability goals. The study emphasizes the importance of integrating ethical principles, such as justice (adl), beneficence (ihsan), and accountability (amanah), into curriculum design to foster responsible global citizens. Theoretical framework: The theoretical framework combines Islamic epistemological principles with the humanistic educational model, illustrating how ethical dimensions can shape pedagogy, learning outcomes, and societal impact. Literature Review: The literature review highlights the convergence of ethical frameworks in Islamic education with contemporary educational theories. Key references include works on Islamic epistemology, ethics, and SDG-related educational initiatives. This review identifies gaps in current curriculum models that fail to emphasize ethical values as foundational elements. Methods: A qualitative research method was employed, involving content analysis of Islamic epistemological texts, curriculum policies, and case studies from Islamic educational institutions. Data were gathered through document analysis and interviews with curriculum experts, educators, and policymakers. Results: The findings reveal that integrating Islamic epistemology into curriculum development fosters holistic education, bridging spiritual, intellectual, and social dimensions. Such integration enhances moral responsibility, critical thinking, and sustainable practices among learners. Implications: The implications of this study are significant for policymakers and educators seeking to design curricula that align with SDG principles. By emphasizing ethical values, the proposed framework promotes inclusivity, environmental stewardship, and social justice, directly contributing to Goals 4 (Quality Education) and 16 (Peace, Justice, and Strong Institutions). Novelty: The study's novelty lies in offering a structured approach to ethical curriculum development grounded in Islamic epistemology, addressing both spiritual and material dimensions of education. It advocates for a paradigm shift where ethics is not merely an addition but a core component of curriculum design.